Relevamiento de virus y Spiroplasma kunkelii en lotes de maíz del Valle medio del Río Negro, Patagonia Argentina - Barontini, Javier Miguel; Favere, Verónica Mariela; Ferrer Lanfranchi, Mariana; Colella, E.; Ruiz Posse, Agustina María; Laguna, Irma Graciela; Gimenez, Maria De La Paz; Torrico Ramallo, Ada Karina (Asociación de Ingenieros Agrónomos del Norte de la Provincia de Buenos Aires, 2022)
A survey to determine the presence and incidence of viruses and Spiroplasma kunkelii was conducted in corn fields in the Valle Medio del río Negro, Patagonia, Argentina, during 2021/22. Leaves were collected from random plants from six fields. Symptomatic leaves were collected simultaneously. DAS or PTA ELISA to detect a mollicute and eight maize viruses, such as Maize chlorotic mottle virus (MCMV), Mal de Rio Cuarto virus (MRCV), Sugarcane mosaic virus (SCMV), SCMV variant JM, Maize dwarf mosaic virus (MDMV), Maíz rayado fino virus (MRFV), Wheat streak mosaic virus (WSMV), and High plains wheat mosaic virus (HPWMoV) confirmed the presence of all pathogens except MCMV. Simple and multiple viral infections were observed. S. kunkelii incidence was 4%, while MRCV incidence was 17%. In the Valle Medio del río Negro region, S. Kunkelii was detected with a low incidence rate. High prevalence of MRCV and HPWMoV were recorded and the presence of viruses in simple and multiple infections of up to four pathogens in the same maize plant was determined.